1998
DOI: 10.1530/jrf.0.1140287
|View full text |Cite
|
Sign up to set email alerts
|

Luteinization and proteolysis in ovarian follicles of Meishan and Large White gilts during the preovulatory period

Abstract: (Legault and Caritez, 1983;Bolet et al, 1986). This appears to be largely due to an altered embryonic growth and improved embryonic development and survival (Bazer et al, 1988(Bazer et al, , 1991 Simmen et al, 1989;Wilmut et al, 1992;Anderson et al, 1993) Immunostaining was performed according to the method described by Meduri et al. (1996). This method is based on the formation of a streptavidin-biotin complex using the Vectastain ABC kit (Vector Laboratory, Burlingame, CA).Sections were rinsed in 10 mmol PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…In the present study, we assessed the gelatinase levels in the follicular fluid of women with unexplained infertility who received IVF treatment and investigated the relationship between oocyte quality and fertilization. The presence of gelatinases in follicular fluid suggests that they are essential during follicular growth and development [16]. The gene expression and protein activity of gelatinases reportedly increase during follicular development [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we assessed the gelatinase levels in the follicular fluid of women with unexplained infertility who received IVF treatment and investigated the relationship between oocyte quality and fertilization. The presence of gelatinases in follicular fluid suggests that they are essential during follicular growth and development [16]. The gene expression and protein activity of gelatinases reportedly increase during follicular development [16].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of gelatinases in follicular fluid suggests that they are essential during follicular growth and development [16]. The gene expression and protein activity of gelatinases reportedly increase during follicular development [16]. Bagavandoss et al [17] reported that the presence of MMP-2 in the neonatal ovary suggests that it functions in follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NR5A2 (liver receptor homolog-1), a transcription factor that activates transcription of steroidogenic genes, including aromatase (Sirianni et al 2002, Mendelson et al 2005 was also greater in preovulatory estrogenic follicles. 3-b-Hydroxysteroid dehydrogenase (3b-HSD) increased in preovulatory luteinized follicles; a change in gene expression that is known to occur during luteinization (Conley et al 1995, Driancourt et al 1998. There was also a predictable change in INHBB, AKR1C3, and PTGES (inhibin, b-B, prostaglandin F synthase, and prostaglandin E synthase; high in preovulatory follicles; Jiang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The final functional class that was differentially expressed in preovulatory luteinized follicles was comprised of genes whose proteins play a role in angiogenesis. The process through which angiogenesis is initiated within the luteinized follicles has been described (Murphy et al 2001) and is of interest because of the rapid development of a vascular bed in the growing corpus luteum (Driancourt et al 1998.). Two of the enzymes in this group (MAOB and LAP3) are vasodilatory; monoamine oxidase metabolizes vasoactive amines to inactive forms and is found in high amounts within the preovulatory follicle and corpus luteum (Yoshimoto et al 1986) and LAP3 (also known as cysteine amino peptidase or oxitocinase) metabolizes oxytocin, vasopressin, and angiotensin III (Tsujimoto & Hattori 2005) and is a marker for malignant gynecological tumors (Ino et al 2004).…”
Section: Genbankmentioning
confidence: 99%
“…Matrix metalloproteinase-9 was elevated in fluid of preovulatory follicles of pigs [95] and horses [96] and in formative corpora lutea or luteinized granulosa cells of rats [97], cattle [98,99], and human beings [100]. Collagenase-3 (MMP-13), which degrades collagens I-III, was increased in preovulatory rat follicles [101,102].…”
Section: Additional Considerationsmentioning
confidence: 99%